Richness of Phytoplankton and Zooplankton in Water Streams at Jobolarangan Forest - ARI SUSILOWATI; WIRYANTO WIRYANTO; AINUR ROHIMAH (Biodiversitas Journal of Biological Diversity, 2001)
Plankton is components of aquatic ecosystem. Phytoplankton play as primary producers, zooplankton play an important role in the higher order in the transfer of energy primary producers, the alga, to the higher order consumers such as aquatic insects, larval fish, and some adult fish. Streams of Jobolarangan forest may show phytoplankton and zooplankton that unique. The objectives of this research were to know diversity of phytoplankton and zooplankton and to determined their density. Plankton were sampled using 25-30 Î¼m mesh net, in three location of streams, i.e.: Parkiran (1773 m asl.), Mrutu (1875 m asl.), and Air Terjun (1600 m asl.). Samples were examined under light microscope for identification, and determined their density/L. Richness of phytoplankton in streams at Jobolarangan forest composed by family of Chlorophyceae, Euglenophyceae (Algae), and Bacillariophyceae. Zooplanktons that were found order of rotifer, cladoceras, and copepods. Allochtonous productivity, low nutrient level, low light level, and flowing water condition caused density of plankton/L in stream at Jobolarangan was low, i.e. 0,064 to 0,232.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: plankton, Jobolarangan, richness, diversity.